(untitled) (Global Journal of Medical Research, 2020)
Introduction: Severe open injuries of limbs, especially of the femur and tibia when associated with vascular injuries, present major challenges in management. The decision to amputate or salvage can often be a difficult one even for experienced surgeons. Mangled lower extremity results due to high energy trauma especially due to motor vehicle accidents and is defined as injury to three of the four systems in the extremity i.e soft tissues, bone, vascular and nerve. Open fractures are classified by Gustilo and Anderson’s classification in which type 3b is a injury where soft tissue loss and primary closure of the wound is not possible and type 3c is any open fracture with vascular compromise.